Revealing Lipid Body Formation and its Subcellular Reorganization in Oleaginous Microalgae Using Correlative Optical Microscopy and Infrared Nanospectroscopy. Issue 12 (December 2021) - Deniset-Besseau, Ariane; Coat, Rémy; Moutel, Benjamin; Rebois, Rolando; Mathurin, Jérémie; Grizeau, Dominique; Dazzi, Alexandre; Gonçalves, Olivier
The purpose of this work is to develop an integrated imaging approach to characterize without labeling at the sub-cellular level the formation of lipid body droplets (LBs) in microalgae undergoing nitrogen starvation. First conventional optical microscopy approaches, gas chromatography, and turbidimetry measurements allowed to monitor the biomass and the total lipid content in the oleaginous microalgae Parachlorella kesslerii during the starvation process. Then a local analysis of the LBs was proposed using an innovative infrared nanospectroscopy technique called atomic force microscopy-based infrared spectroscopy (AFM-IR). This label-free technique assessed the formation of LBs and allowed to look into the LB composition thanks to the acquisition of local infrared spectra. Last correlative measurements using fluorescence microscopy and AFM-IR were performed to investigate the subcellular reorganization of LB and the chloroplasts. Graphical Abstract